2020
DOI: 10.1037/cdp0000326
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and gender differences in the antecedents of youth suicide.

Abstract: Objectives: This study examined racial/ethnic and gender differences in the antecedents of adolescent suicide deaths in the United States. Method: Using postmortem data (N = 3,996, mean age = 16.01, 77% male) from the National Violent Death Reporting System, the authors investigated whether White, Black, Native American, Asian Pacific Islander American, and Latinx youths aged 10 to 18 varied in their rates of circumstances that either preceded or appear to have contributed to their suicides. Gender differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…For instance, adolescents of color can face uniquely harmful effects of biasbased peer victimization, or disproportionate levels of contextual-level risk factors linked to peer victimization (eg, adverse school environments). 15 For suicidal outcomes, not only do the factors contributing to suicidal behavior vary across racial and ethnic categories, 16 but the prevalence of these outcomes varied across racial and ethnic groups in YRBS data. 17 These prevalence disparities also occurred by sex, with girls having higher levels of both suicidal outcomes and peer victimization.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, adolescents of color can face uniquely harmful effects of biasbased peer victimization, or disproportionate levels of contextual-level risk factors linked to peer victimization (eg, adverse school environments). 15 For suicidal outcomes, not only do the factors contributing to suicidal behavior vary across racial and ethnic categories, 16 but the prevalence of these outcomes varied across racial and ethnic groups in YRBS data. 17 These prevalence disparities also occurred by sex, with girls having higher levels of both suicidal outcomes and peer victimization.…”
Section: Methodsmentioning
confidence: 99%
“…Goal Theory helped to inform how coaches worked with students to set weekly and overall goals. The application of Goal Theory was intended to optimize youth's potential for reaching their goal by guiding them to identify and select their own unique goal that is relevant, important, and feasible to attain, while also incorporating a feedback mechanism (i.e., check-ins and discussions between youth and health coaches) (Latham & Locke, 1991). In addition, discussions and goal-setting activities were framed within the social-ecological model, which theorizes that behaviors are inherently influenced by and across multiple levels of one's social environment (i.e., intrapersonal, interpersonal, organizational, community, and public policy) (Stokols, 1996).…”
Section: Interventionmentioning
confidence: 99%
“…Rates of death by suicide among youth aged 10–24 years increased by 56% from 2007 to 2017 (Curtin, 2020 ; Curtin & Hedegaard, 2019 ; Lee & Wong, 2020 ; Oh et al, 2019 ). In parallel to the increasing prevalence of youth suicide, there has been a rapid increase in youth diagnosed with depression (Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural considerations are warranted in the design of preventative interventions. Research has found substantial gender and racial/ethnic differences in suicide risk factors among youth underscoring the need for this ( Lee and Wong, 2020 ). Recommendations for interventions tailored to the black community include efforts to increase access to mental health care by reducing stigma and increasing help-seeking behavior ( Lindsey et al., 2019 ).…”
Section: Current and Future Strategies For Prevention Intervention mentioning
confidence: 99%